Non-tuberculous Mycobacterium Disease: Radiologic Manifestation in an Infant presenting with Respiratory Distress - Gautam, Rupesh; Atienza, Maria Isabel; Noda, Maika; Andres, Mariaem (Nepalese Journal of Radiology, 2017)
Non-tuberculous mycobacterium (NTM) comprises distinct group of organisms with lymphadenitis and pulmonary infection as the common manifestation. The diagnosis of pulmonary disease is based on clinical manifestations, radiologic findings and microbiologic culture. The classic NTM infection may be indistinguishable from pulmonary TB. Non-classic infection has predilection to the middle lobe and lingula unlike tuberculosis which is commonly seen in the upper lobes. The disease may also present as hypersensitivity pneumonitis with ground glass like opacities, centrilobular nodules and air trapping on imaging. The knowledge of imaging manifestations of NTM will aid in timely diagnosis and treatment of the disease. Nepal Journal of Radiology Vol.5(1-2) 2015: 13-20